Assessing the Effects of Packed Beds on Lautering Performance and Wort Quality - Bandelt Riess, Peter Michael; Bertazzoni Streit, Johann Alberto; Kuhn, Michael; Briesen, Heiko; Först, Petra (BrewingScience, 2021)
The production in a brewery can be considerably affected by the lautering performance. To counteract inefficiencies and accelerate this operation, a novel process strategy is applied and evaluated. The incorporation of additional wall support by using different configurations of packed beds is studied in a laboratory setup. As a result, the compressibility of the filter cake is greatly reduced, and the wort flow through it is improved. Significant lautering time savings of 75% are achieved through a specific type of packing without sacrificing wort quality. These findings might help brewers to modernize the lauter tun and increase production capacity.